2016
DOI: 10.3390/v8110278
|View full text |Cite
|
Sign up to set email alerts
|

Kaumoebavirus, a New Virus That Clusters with Faustoviruses and Asfarviridae

Abstract: In this study, we report the isolation of a new giant virus found in sewage water from the southern area of Jeddah (Saudi Arabia), with morphological and genomic resemblance to Faustoviruses. This new giant virus, named Kaumoebavirus, was obtained from co-culture with Vermamoeba vermiformis, an amoeboid protozoa considered to be of special interest to human health and the environment. This new virus has ~250 nm icosahedral capsids and a 350,731 bp DNA genome length. The genome of Kaumoebavirus has a coding den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 31 publications
(43 reference statements)
2
91
0
Order By: Relevance
“…Indeed, with faustovirus and kaumoebavirus analyses (15,16), we observed that small coding sequences were conserved and may encode elements constituting the viral capsid. Finally, in the absence of transcriptomic and proteomic analyses, we decided to keep 465 genes in the pacmanvirus gene repertoire, which represents a coding density of about 89.3% along the 353,121 bp (mean GC% of the coding sequences Ϸ 34.7%).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Indeed, with faustovirus and kaumoebavirus analyses (15,16), we observed that small coding sequences were conserved and may encode elements constituting the viral capsid. Finally, in the absence of transcriptomic and proteomic analyses, we decided to keep 465 genes in the pacmanvirus gene repertoire, which represents a coding density of about 89.3% along the 353,121 bp (mean GC% of the coding sequences Ϸ 34.7%).…”
Section: Resultsmentioning
confidence: 91%
“…The major capsid protein is encoded in a single ORF in pacmanvirus and ASFV, while it is located in different loci in the case of kaumoebavirus and faustoviruses. We do not know if this process is related to host range as for the double protein capsid studied for faustovirus (15,17,19) and the predicted capsid protein of kaumoebavirus (16). Despite all this, the ASFV virion structure includes an outer lipid membrane, an icosahedral protein capsid, and an inner lipid membrane (29) that is strongly involved in cell infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of their genomes have revealed homology with Asfarviridae and kaumoebavirus, suggesting a shared origin (2, 3). Here, we report the complete genome sequence of faustovirus strain ST1 and the draft genome annotation of faustovirus strain LC9.…”
Section: Genome Announcementmentioning
confidence: 99%